2019
DOI: 10.1001/jamadermatol.2019.2890
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Survival After Mohs Micrographic Surgery vs Wide Margin Excision for Early-Stage Invasive Melanoma

Abstract: IMPORTANCE Melanoma is among the most common malignant neoplasms in the United States, with 91 270 cases estimated to be diagnosed in 2018. Since 2012, Mohs micrographic surgery (MMS) has gained popularity in the treatment of melanoma in situ. Although current guidelines for invasive melanoma without nodal metastases recommend surgery with wide margin excision (WME), use of MMS for this disease has increased as well, particularly in early stages. How the survival outcomes after each procedure compare with one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 36 publications
3
70
0
Order By: Relevance
“…Some studies have found that the most common location of malignant melanoma in women is the lower limb, while that in men is the trunk. The surgical margins and external stresses differ in various parts of the body, which may lead to differences in prognosis (14)(15)(16)(17). Our baseline data also confirm this distribution difference.…”
Section: Discussionsupporting
confidence: 77%
“…Some studies have found that the most common location of malignant melanoma in women is the lower limb, while that in men is the trunk. The surgical margins and external stresses differ in various parts of the body, which may lead to differences in prognosis (14)(15)(16)(17). Our baseline data also confirm this distribution difference.…”
Section: Discussionsupporting
confidence: 77%
“…The technique eliminates uncertainty about the status of the primary melanoma because it allows same‐day excision and comprehensive margin assessment immediately before reconstruction. The efficacy of MMS‐IHC has been confirmed by numerous retrospective cohorts, with local recurrence rates <1%, 11‐14 and the technique's safety has been supported by several large, multiinstitutional database studies showing equivalent or improved survival after MMS‐IHC versus WLE 10,15‐18 . Consequently, the use of MMS‐IHC for melanoma has grown steadily over the last 2 decades.…”
Section: Introductionmentioning
confidence: 92%
“…One method to assess the complete histologic margins before reconstruction is Mohs micrographic surgery with frozen‐section immunohistochemical stains (MMS‐IHC) 10 . The technique eliminates uncertainty about the status of the primary melanoma because it allows same‐day excision and comprehensive margin assessment immediately before reconstruction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations